Austerity, cyclical adjustment and the remaining leeway for expansionary fiscal policies in the Euro area - Achim Truger (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2014)
Fiscal policy in the Euro area is still dominated by austerity measures implemented under the institutional setting of the 'reformed' stability and growth pact, and the even stricter 'fiscal compact'. At the same time, calls for a more expansionary fiscal policy to overcome the economic crisis have become more frequent, recently. Therefore, the article tries to assess the remaining leeway for a truly expansionary fiscal policy within the existing institutional framework. Special emphasis is put on the method of cyclical adjustment employed by the European commission in order to assess member states' fiscal position and effort. It turns out that even in the existing framework the leeway for a macroeconomically and socially more sensible fiscal policy using the interpretational leeway inherent in the rules is quite substantial.
urn:nbn:de:101:1-201411242641
Keywords: E61; E62; E65; H62; H63; 330; fiscal policy; austerity; cyclical adjustment of public finances; Euro area